Rôle historique de la station Missionnaire Baptiste (BMS) de Yalikina dans le développement du Territoire d’ISANGI - Jérôme GEOLOLO BAPOWA, (IJRDO - Journal of Social Science and Humanities Research, 2020)
The Baptist Missionary station (BMS) Yalikina has been created in 1912 by gentleman MILL, Yalikina is the first missionary station founded currently after Yakusu in 1895 during the time colonial Belgian in the High Congo in the Province of the Tshopo in territory of Isangi. His/her/its implantation caused a foisonnement of development of the territory of Isangi on all aspects of life (spiritual, state of mind, cultural, socioeconomic, sanitary etc.) because a parish implanted in a middle is a factor of development.